SWOT ANALYSIS IN THE IMPLEMENTATION OF THE TRIJAYA FM RADIO NEWS PORTAL - Misia, Trivena; Sinaga, Tantri Hidayati; Rahayu, Eka (Cattleya Darmaya Fortuna, 2025)
Radio MNC Trijaya 95.1 FM is a radio station that broadcasts the latest news in Indonesia. This research aims to create a broadcast information system on Radio MNC Trijaya 95.1 FM which provides a radio broadcast service system as well as news and song request facilities offered via the internet, and can be an online promotional media that can be accessed anytime and anywhere. To achieve the research objectives, data collection methodologies were used, such as direct observation, interviews and questionnaires. Then analyze the problem using the SWOT analysis method, and create a proposed system design that will be built using the RAD (Rapid Application Development) method, and the programming languages used are PHP and JavaScript. The database uses MySQL. The tools and editors used are XAMPP for Windows, Notepad++. The result of this research is to design a radio broadcasting information system on radio that can help listeners of Radio MNC Trijaya 95.1 FM in accessing information such as broadcast schedules, news and events, broadcaster profiles, and song requests.